Mal is not esential for TLR2 signalling and inhibits signalling by TLR3 - Kenny, Elaine (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2010)
This thesis set out to systematically analyse the role of Mai in signalling by TLR2, TLR3 and TLR4 in murine macrophages and dendritic cells. It has revealed that Mai is not essential to TLR2 signal transduction, is required for TLR4 signalling and is inhibitory for signalling by TLR3. The absolute requirement for MyD88 in TLR2 and TLR4 signalling was also confirmed.
Keywords: Biochemstry, Ph.D.; Ph.D. Trinity College Dublin.